2017
DOI: 10.1016/j.jss.2017.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Use of axillary lymph node dissection (ALND) in patients with micrometastatic breast cancer

Abstract: Given that the risk of lymphedema after ALND ranges between 20%-53%, the morbidity of ALND may far exceed the likelihood of detecting further nodal involvement in women with micrometastatic disease: 7.1% in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…In this study, 54.1% of the patients had one to two SLNs removed, which was similar to previous research [ 26 , 30 , 36 ]. Moreover, the median and range of SLNs in our study were also consistent with previous research [ 17 , 24 , 26 , 27 , 29 , 30 , 36 ]. However, two studies showed both a higher median number and wider range [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, 54.1% of the patients had one to two SLNs removed, which was similar to previous research [ 26 , 30 , 36 ]. Moreover, the median and range of SLNs in our study were also consistent with previous research [ 17 , 24 , 26 , 27 , 29 , 30 , 36 ]. However, two studies showed both a higher median number and wider range [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, two studies showed both a higher median number and wider range [ 37 , 38 ]. Regarding the micrometastatic SLNs, most studies have indicated an extremely high percentage of one and two positive SLNs [ 17 , 24 , 30 , 39 ], and several studies selected one as a cut-off point [ 36 , 37 , 40 ] without demonstrating additional details concerning the low quantity; other studies have shown no more than two invaded [ 25 , 27 , 29 ]. The relative small probability to discover three micrometastases in SLNs was caused by the low number of SLN examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly after the introduction of SLNB, the use of ALND in the management of breast cancer declined dramatically since SLNB proved to be a non-inferior staging procedure [10][11][12][13][14]. Furthermore, cALND as a standard procedure after a positive SLNB became a matter of debate since it showed no survival benefit [4,5,8,15]. Recently, axillary radiotherapy has been introduced as an alternative treatment to the axilla after a positive SLNB [4,16].…”
Section: Discussionmentioning
confidence: 99%
“…A number of trials have confirmed that the incidence of upper limb edema, numbness, pain, paresthesia, shoulder joint mobility disorder and other complications in SLNB patients is significantly lower than that of ALND, which improves the quality of life of patients. [8,9] In the 8th edition of the American Joint Committee on Cancer (AJCC) [10] breast cancer staging, the number of SLNs was less than 6, and SLN footnote “sn” could not be used if there were more than 6. But the minimum number of SLNs is not specified.…”
Section: Introductionmentioning
confidence: 99%